Dental participation in geriatric interprofessional education courses: A systematic review. (30th March 2018) - Kossioni, A. E.; Marchini, L.; Childs, C.
Abstract: Introduction: Although the interdisciplinary management of the ageing individual is highly stressed, there is limited information on the outcomes of interprofessional education (IPE) activities of dental students in geriatrics. This systematic review aimed to identify studies with dentists participating in formal IPE courses in geriatrics and assess the outcomes reported. Material and Methods: Electronic databases (PubMed, EMBASE, CINAHL and Scopus), reference lists from relevant studies and cited papers were investigated. The inclusion criteria were as follows: about formal interactive learning; learners from at least 2 disciplines; including dentists; related to geriatrics; any study design; reporting any outcome; only full papers; published in peer‐reviewed journals; English language. Results: Of the 1259 records retrieved, 26 were assessed for eligibility based on defined inclusion criteria and 7 studies were included in the final analysis. Two studies reported specific outcomes for dentists with lower, or even negative, post‐training scores for interprofessional collaborative practice competences compared to other disciplines, but only one of them used a previously validated scale. There were no reports on the effect of IPE courses on dental trainees' gerodontology skill improvements or on their attitudes towards the older persons. Conclusion: The existing evidence is insufficient to determine any outcomes of formal interprofessional training of dentists in geriatrics. More studies with better experimental design should be developed. Among the strengths of IPE in geriatrics are the interdisciplinary nature of geriatric care, the sharing of common geriatric competences among participating disciplines and the opportunity to use nursing homes as a training site.